2005
DOI: 10.1248/yakushi.125.159
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Pharmaceutical Services from the Viewpoint of Patient Satisfaction/Dissatisfaction

Abstract: A survey was conducted to examine what the public expects of pharmacists. We created 26 questions based on 26 diŠerent situations that patients encounter at pharmacies in order to assess patient satisfaction/dissatisfaction. Some questions were designed to compare pairs of symmetrical situations. The survey was carried out in February and March 2001. The surveys were conducted with patients and/or patients' relatives who brought their prescriptions to pharmacies and with employees of pharmaceutical companies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…As mentioned above, the previous studies at pharmacies demonstrated that patients visiting pharmacies considered the expertise and the pharmacy’s location as the most important [2,6,7,9,10,11]. The current study revealed that the functional difference between drug stores and pharmacies had some effects on the structure of customers’ demands.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…As mentioned above, the previous studies at pharmacies demonstrated that patients visiting pharmacies considered the expertise and the pharmacy’s location as the most important [2,6,7,9,10,11]. The current study revealed that the functional difference between drug stores and pharmacies had some effects on the structure of customers’ demands.…”
Section: Discussionsupporting
confidence: 50%
“…Surveys on medical facilities were mainly conducted at hospitals and pharmacies [1,2,3,4,5,6,7,8,9,10,11]. However, there have been few reports about surveillance at drug stores.…”
Section: Introductionmentioning
confidence: 99%
“…Hayashi et al 18 hypothesized that "expressive" satisfaction occurs when a pharmacy service is "not strongly required but desirable." However, if some patients question whether pharmacists should be operating in territory that is perceived to be beyond their recognized and legitimate role, then it might be expected that satisfaction could be lower.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the attitude of the pharmacist and specialized activities such as providing information and explanations and the convenience of opening hours are not only judged to be important by patients but also influence their satisfaction [9,10]. The ultimate goal of patient satisfaction is to improve patient care.…”
Section: Introductionmentioning
confidence: 99%